Evaluation of the Ecochemical Status of the Danube in Serbia in Terms of Water Quality Parameters - Ljiljana Takić; Ivana Mladenović-Ranisavljević; Milovan Vuković; Ilija Mladenović (The Scientific World Journal)
The Danube is an international river passing partly through Serbia. The protection of the environment and sustainable use of water resources is a primary task that implies constant monitoring of the quality status and evaluation of ecochemical status of the water in the Danube basin. The investigation includes calculation of all-inclusive water quality by the Serbian water quality index (SWQI) method and an evaluation of eco-chemical status of the Danube water in terms of water quality parameters from the entry to the exit point along its course through Serbia in the year of 2009. The results show that the overall quality of the Danube water on the territory of Serbia corresponds to the descriptive indicator of “very good” water. According to the Council Directive 75/440/EEC, the evaluation of the ecostatus, with slight deviation of individual parameters at Pančevo, corresponds to A1 category of the surface water quality intended for the abstraction of drinking water supplies in member states.